2014
DOI: 10.1016/j.addbeh.2013.10.034
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute exercise on tobacco cravings and withdrawal symptoms in temporary abstinent pregnant smokers

Abstract: Introduction-Smoking during pregnancy is common, and quitting at any point during pregnancy can yield benefits to both the fetus and mother. Smoking cessation is typically followed by withdrawal symptoms and a strong desire to smoke, both of which are likely to contribute to relapse. Research has shown that a bout of exercise minimizes cravings and tobacco withdrawal symptoms (TWS) after temporary abstinence in smokers, but these findings have not been replicated in pregnant smokers. This study examined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Indeed, results from a recent meta-analysis showed that aerobic and mind-body exercise produced similar effects on withdrawal symptoms, drug-craving, and depression (9). While higher intensity exercise may induce greater effects (20,26), even light intensity exercise, such as walking, can induce beneficial effects (1416,20,26). Indeed, preliminary findings show that both walking and jogging decrease craving in women and men with concurrent cocaine and tobacco-use disorder although effects did not reach statistical significance in this pilot study (26).…”
Section: Overview Of Clinical Findingsmentioning
confidence: 99%
“…Indeed, results from a recent meta-analysis showed that aerobic and mind-body exercise produced similar effects on withdrawal symptoms, drug-craving, and depression (9). While higher intensity exercise may induce greater effects (20,26), even light intensity exercise, such as walking, can induce beneficial effects (1416,20,26). Indeed, preliminary findings show that both walking and jogging decrease craving in women and men with concurrent cocaine and tobacco-use disorder although effects did not reach statistical significance in this pilot study (26).…”
Section: Overview Of Clinical Findingsmentioning
confidence: 99%
“…The value of results obtained by us on a sample of 481 subjects is closest to values coming from a neighboring region, following the study conducted by Meghea et al, respectively the prevalence of smoking during pregnancy by a value of 12.88 % [18].…”
Section: Discussionmentioning
confidence: 66%
“…As a result of data collected has been identified 26 % women consumers of tobacco before pregnancy period but which have renounced as soon as they found that they are pregnant, while about 15 % continued to smoke during pregnancy [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, a low dose of nicotine, as found in NRT options, still has negative health implications including inducing a hypoxic fetal environment and maternal hypertension (46) Exercise interventions have the potential to reduce cravings and withdrawal symptoms without increasing the risk for maternal or fetal adverse events. To date, only one study provides evidence that acute exercise during pregnancy reduces smoking cravings (51). The effectiveness of exerciseaided smoking cessation programs have produced mixed results in the non-smoking population and one study found no support for these type of programs in pregnant smokers wanting to quit (65).…”
Section: Discussionmentioning
confidence: 99%
“…To date, Prapavessis et al, (51) are the only research group to our knowledge to design a study examining the possibility of relieving cravings in the pregnant population with an acute bout of exercise. Pregnant women are an especially vulnerable group to withdrawal symptoms and cravings because their cravings are expedited by a faster metabolism of nicotine during pregnancy (43).…”
Section: Acute Effects Of Exercise On Cravings and Withdrawal In Pregmentioning
confidence: 99%